Not Space-Ninjas Again!: Transmedia Worldbuilding for Social Justice - Sturrock, Ian (Gamevironments, 2022)
In this report, I briefly survey some of the frequently problematic remediation of real-world cultures into fictional races, in fantasy and science fiction games. I argue that the process of designing fantasy character cultures, as part of the wider worldbuilding process, is in need of a major rethink if principles of anti-oppression are to be followed. The frequently problematic depictions of female characters, and the remediation of real-world cultures into fictional races, in fantasy games and other fantasy fiction, are explored in a close reading of the biggest name in fantasy computer gaming, World of Warcraft (2004). I then offer tools, techniques, and principles for practical worldbuilding of fictional cultures and religions that will both avoid the appropriative practices that are the mainstay of most worldbuilding, and create more original and compelling fictional settings. These techniques are derived from a combination of literature research into existing recommendations on anti-oppressive game design; conversations with working games artists and game designers; teaching methods derived from teaching practical worldbuilding and games narrative design on several courses at different universities; and my PhD thesis, the conclusions of which included suggestions as to a code of practice on ethical game design. A step-by-step worked example is included: a fictional culture that is verisimilitudinous without being clearly based on a specific real-world culture. This makes for an effective starting point for anti-oppressive worldbuilding, as well as tying in with principles of user-centric design: settings created in this manner come across as fresh and original, without the often problematic clichés of yet another remediation of Dungeons and Dragons (hereafter D&D) (1974) remediating Tolkien. These tools and techniques allow for the creation of fictional settings that are not only grounded in principles of anti-oppressive game design but also powerfully verisimilitudinous in a way that World of Warcraft, for example, is clearly not. Despite the gamer community’s frequently expressed fears of censorship by the social justice movement, this kind of approach to design would create better and more original art, freed from the conservative remediation-upon-remediation culture of conventional fantasy and science fiction game designs.